Immune deficiency: changing spectrum of pathogens. (August 2015) - Duraisingham, S. S.; Manson, A.; Grigoriadou, S.; Buckland, M.; Tong, C. Y. W.; Longhurst, H. J.
Summary Current UK national standards recommend routine bacteriology surveillance in severe antibody‐deficient patients, but less guidance exists on virology screening and viral infections in these patients. In this retrospective audit, we assessed the proportion of positive virology or bacteriology respiratory and stool samples from patients with severe, partial or no immune deficiency during a 2‐year period. Medical notes were reviewed to identify symptomatic viral infections and to describe the course of persistent viral infections. During the 2‐year period, 31 of 78 (39·7%) severe immune‐deficient patients tested had a positive virology result and 89 of 160 (55.6%) had a positive bacteriology result. The most commonly detected pathogens were rhinovirus (12 patients), norovirus (6), Haemophilus influenzae (24), Pseudomonas spp. (22) and Staphylococcus aureus (21). Ninety‐seven per cent of positive viral detection samples were from patients who were symptomatic. Low serum immunoglobulin IgA levels were more prevalent in patients with a positive virology sample compared to the total cohort (P = 0·0078). Three patients had persistent norovirus infection with sequential positive isolates for 9, 30 and 16 months. Virology screening of symptomatic antibody‐deficient patients may be useful as a guide to anti‐microbial treatment. A proportion of these patients may experience persistent viral infections with significant morbidity.